Implementasi Nilai-Nilai Moderasi Beragama dalam Pembelajaran Pendidikan Agama Islam Siswa Kelas VIII di SMPN 1 Batang Angkola Kabupaten Tapanuli Selatan - Nur Adinda Siregar; Muhammad Royhan Daulay (SURAU : Journal of Islamic Education, 2025)
Indonesia is a country characterized by religious, ethnic, and cultural diversity, which constitutes a strategic asset in national and civic life. However, such diversity may also pose challenges to maintaining national unity if it is not properly managed. Therefore, instilling the values of religious moderation from an early age, particularly through educational settings, is essential. This study aims to examine the values of religious moderation in Islamic Religious Education (IRE) learning and to analyze their implementation among eighth-grade students at SMP Negeri 1 Batang Angkola, South Tapanuli Regency. This research employs a qualitative approach, with data collected through observation, interviews, and documentation. The findings indicate that the values of religious moderation have been implemented in Islamic Religious Education learning; however, the implementation has not been optimal or fully integrated. Islamic Religious Education teachers still face limitations in systematically internalizing these values within the learning process. The identified values of religious moderation include openness, simplicity, tolerance, justice, as well as unity and brotherhood. These findings highlight the need to strengthen the planning of Islamic Religious Education learning based on religious moderation in order to foster inclusive, tolerant, and socially ethical attitudes among students.